Use of dialogue in Dibabawon narrative discourse - Forster, Jannette (Philippine Journal of Linguistics, 1983)
The purpose of this paper is to examine the use of dialogue as a strategy for building tension in a Dibabawon factual narrative discourse. l The discussion will deal mainly with one such discourse, with a less detailed look at a second discourse in Section 3 of the paper. The text from which most of the data are drawn is a first person narrative, written by a man in his early 30's, recalling both the events and the emotions he experienced the first time he attended school. The discourse begins with an expository paragraph in which the author introduces a problem. The remainder of the discourse comprises four episodes which rely heavily on dialogue to further define the problem and to set forth the solution. The progression of excitement in dialogue paragraphs is reflected in the author's choice of quotation types. These range from narrative dialogue, in which dialogue is introduced by a quotation formula, to dramatic dialogue, in which there is no quotation formula to signal change of speaker.2 Within narrative dialogue there is 'a contrast of tension shown in the quotation formulas: an inflectional quotation formula in which the speech verb has the same time aspect affixation as other independent verbs in the paragraph is less vivid than a reduced quotation formula in which the speech word is unaffixed. Thus for this .text I posit a scale of vividness3 with three levels: 1 - no quotation formula 2 - reduced quotation formula 3 - inflectional quotation formula.